Racial disparity in utilization of therapeutic modalities among multiple myeloma patients: a SEER‐medicare analysis. (3rd November 2017) - Ailawadhi, Sikander; Frank, Ryan D.; Advani, Pooja; Swaika, Abhisek; Temkit, M'hamed; Menghani, Richa; Sharma, Mayank; Meghji, Zahara; Paulus, Shumail; Khera, Nandita; Hashmi, Shahrukh K.; Paulus, Aneel; et al.
Abstract: Outcomes have improved considerably in multiple myeloma (MM), but disparities among racial‐ethnic groups exist. Differences in utilization of novel therapeutics are likely contributing factors. We explored such differences from the SEER‐Medicare database. A utilization analysis of lenalidomide, thalidomide, bortezomib, and stem cell transplant (SCT) was performed for patients diagnosed with MM between 2007 and 2009, including use over time, use by race, time‐dependent trends for each racial subgroup, and survival analysis. A total of 5338 MM patients were included with median 2.4‐year follow‐up. Within the first year of MM diagnosis, utilization of lenalidomide, bortezomib, SCT, and more than one novel agent increased over time while utilization of thalidomide decreased. There was significantly lower utilization of lenalidomide among African‐Americans ( P  <   0.01), higher thalidomide use among Hispanics and Asians ( P  <   0.01), and lower bortezomib use among Asians ( P  <   0.01). Hispanics had the highest median number of days to first dose of bortezomib ( P  =   0.02) and the lowest utilization of SCT ( P  <   0.01). Hispanics and Asians were the only groups without notable increases in lenalidomide and bortezomib use, respectively. SCT utilization increased over time for all except African‐Americans. SCT use within the first year after diagnosis was associated with better overall survival (HR 0.52; 95% CI: 0.4–0.68), while bortezomib use was associated with inferior survival (HR 1.14; 95% CI 1.02–1.28). We noted considerable variability in MM therapeutics utilization with seeming inequity for racial‐ethnic minorities. These trends should be considered to eliminate drug access and utilization disparities and achieve equitable benefit of therapeutic advances across all races. Abstract : Outcomes have improved considerably in multiple myeloma (MM), but disparities among racial‐ethnic groups exist. Within the first year of MM diagnosis, we found significantly lower utilization of lenalidomide among African‐Americans, lower bortezomib use among Asians and the most delayed access to bortezomib as well as lowest utilization of stem cell transplant for Hispanics. There is considerable variability in MM therapeutics utilization with seeming inequity for racial‐ethnic minorities.